Implementing the Cooperative Learning Model with LCD Projector Media to Improve Elementary School Students’ Learning Outcomes - Oktana, Yayik; Hidayaturrahman, Muhammad (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: In the current era of educational technology, integrating interactive media with effective learning models is essential to enhance student engagement and performance, particularly in primary education. Objective: The purpose of this study was to determine the improvement of elementary school students' learning outcomes using the Cooperative Learning model using LCD Projector Media. Methods: This research used the Classroom Action Research method. The sample of this study was grade V students, with a total of 15 students. Data collection using observation, interviews, tests, and documentation. Analysis using qualitative analysis and quantitative analysis. Results: There is an increase in student learning outcomes using a cooperative learning model assisted by LCD projector media in Islamic religious education subjects at SDN 58 Bengkulu Selatan. This improvement can be seen from the pre-cycle data, cycles I and II; each cycle has increased. Conclusion: The combination of the cooperative learning model and LCD projector media is an effective strategy for improving the learning outcomes of elementary school students. Contribution: This research provides more effective learning alternatives by combining cooperative learning models and LCD projector media